KADAR PROTEIN DAN DAYA TERIMA SILKY PUDDING YANG DISUBSTITUSI SUSU KAMBING DAN SUSU SKIM SEBAGAI ALTERNATIF MAKANAN TAMBAHAN BALITA STUNTING - Rochmah, Syifa; Yani, Ahmad; Aminarista, Aminarista (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2018)
Background: Protein intake is one of the risk factors for stunting in toddlers. Milk can contribute protein for stunting in children by 7.67 g/day. Silky pudding which is substituted goat milk and skim milk is expected to be an alternative food supplement with high protein. Objective: Analyze protein levels and the acceptability of silky pudding substituted for goat milk and skim milk. Method: The experimental study used a completely randomized design of one factor, the substitution of goat milk and skim milk. Protein level and acceptability or hedonic tests of 30 untrained panelists were analyzed using the Kruskal Wallis test with Man Whitney's further tests. Result: There was a significant difference (P = 0.043) between the levels of silky pudding protein P1 (skim milk substitution) and silky pudding protein P0 (control of sweetened condensed milk) and silky pudding protein P2 (substitution of goat's milk). However, there were no significant differences between color acceptability (P = 0.746), flavour (P = 0.223), texture (P = 0.606), and flavor (P = 0.315) between silky pudding P1 (skim milk substitution), silky pudding P0 ( control of sweetened condensed milk) and silky pudding P2 (substitution of goat's milk). Conclusion: Substitution of goat milk and skim milk has an effect on increasing silky pudding protein levels but has no effect on silky pudding acceptance.